An Error Analysis of the Perception Based on Accent in Japanese - Arianingsih, A; Musyaafa, M F K (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Japanese has many words that have similar syllables but different meanings. However, for non-native speakers, these differences in meaning are quite difficult to spot as they can only be distinguished by tone also refers to accent. This study aims to analyze the misperception of accents in words with the same syllable. The data collected in this study were conducted through a perception test. These words were categorized based on the error types of the specified syllables. This study’s respondents are 20 students of the 3rd and 5th semester Japanese Department of Universitas Komputer Indonesia in the 2022/2023 academic year. The results showed that accent perception errors in respondents mostly occurred in Odaka accent patterns and many words with accents of 4 mora. Perception errors occur because students are unfamiliar with the vocabulary and accent patterns. This is related to the length of student learning.